Subsídios teórico-metodológicos para a elaboração de um curso de inglês para a área jurídica na modalidade EaD - China, Anna Patrícia Zakem [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study presents the steps to design a course for English for Specific Purposes for law students and legal professionals focused on reading in distance education, called Inglês Jurídico. The course was designed and taught by the author of this research. We intend to make an original contribution in the field - ESP Language Teaching by showing elements that can contribute to design ESP courses for law students and legal professionals in distance education. The research objectives are: a) to survey the theoretical and methodological elements, aiming to design an ESP course for Law students legal professionals focused on reading in distance education b) design an ESP course for law students and legal professionals focused on reading, in distance education. Three data collection instruments were used: a) Needs Analysis questionnaire answered by 91 potential students - 36 Law students and 55 legal professionals b) semi - structured interviews with 5 participants who had answered the Needs Analysis questionnaire, in order to get clarification c) Consulting official document - Diretrizes Curriculares Nacionais do Curso de Graduação em Direito to verify if English classes were part of the curriculum in Law school. In addition to these instruments, dialogues with members of the legal discourse community and the support of a legal specialist also provided information on how and why English is needed. Data analysis deriving from these instruments revealed the needs and desires of the target audience regarding English use, as well as relevant issues to be addressed in ESP courses for Law students and legal professionals. Based on the data from the needs analysis the course program was defined which led to material selection and organizing the teaching units resulting in the course Inglês Jurídico. The process of organizing and writing this work led to reflection which resulted in proposing actions to ...

Neste estudo apresenta-se o percurso para o desenho de um curso de Inglês para Fins Específicos (ESP) para discentes e profissionais da Área Jurídica com foco na habilidade de leitura, na modalidade de EaD, denominado Inglês Jurídico, que foi elaborado e ministrado pela pesquisadora-autora do presente trabalho. Pretende-se, com esse trabalho, apresentar uma contribuição original para a área de Ensino-Aprendizagem de Língua Inglesa na perspectiva ESP, ao mostrar os subsídios que podem auxiliar no desenho de um curso de ESP na Área Jurídica, na modalidade EaD. Os objetivos da pesquisa são: a) fazer o levantamento dos subsídios teórico-metodológicos, visando o desenho de um curso de ESP para discentes de Direito e profissionais da área jurídica com foco na habilidade de leitura, na modalidade EaD; b) desenhar um curso de ESP para discentes de Direito e profissionais da área jurídica com foco na leitura, na modalidade EaD. No levantamento dos dados, foram utilizados três instrumentos de coleta: a) questionário de Análise de Necessidades, aplicado a 91 alunos em potencial - sendo 36 discentes de Direito e 55 profissionais da área jurídica com o objetivo de levantar as necessidades; b) entrevistas semi-estruturadas, com 5 participantes que haviam respondido ao Questionário de Análise de Necessidades, com o propósito de obter esclarecimentos; c) consulta às Diretrizes Curriculares Nacionais do Curso de Graduação em Direito para averiguar as indicações de uso de língua inglesa na formação do curso de Direito. Além desses instrumentos, diálogos com membros da área jurídica e o respaldo de um consultor jurídico contribuíram com informações sobre o uso da língua inglesa na comunidade discursiva jurídica. A análise dos dados, advindos destes instrumentos, levantou as necessidades e os desejos de uso da língua inglesa do público-alvo, assim como os conteúdos relevantes a serem abordados em um curso de ESP na...
Keywords: Linguistica aplicada; Língua inglesa - Estudo e ensino; Lingua inglesa - Ingles tecnico; Direito - Linguagem; Ensino a distância - Ensino auxiliado por computador; Tecnologias de informação e comunicação